Upaya Meningkatkan Prestasi Belajar Dengan Model Pembelajaran Kooperatif Tipe Jigsaw Pada Mata Pelajaran Ips Siswa Kelas Iii Min Ngestiharjo - Sukati, Sukati (Universitas Alma Ata, 2014)
The type of this research is the Classroom Action Research (CAR). The subjects of this study were students of grade III MIN Ngestiharjo, Wates, Kulon Progo, 40 students in the second semester of the academic year 2013/2014. The object of the study is activities that occur in the classroom during the learning process. This CAR is done by two cycles, each cycle consisting of one meeting. Data were obtained from the observation, interviews, test results and documentation. The data were analyzed with descriptive qualitative through several stages of data analysis of implementation of learning, student achievement data analysis to describe the activities of students and conclusion. The validity of the data is done by asking the opinion of the experts (expert judgment). The results showed that by using a jigsaw cooperative learning model, the learning takes place smoothly by using a five-stage cooperative jigsaw that is read, the expert group discussions, group reports, tests and awards groups. Based on the analysis that model can improve student achievement. Improving learning achievements can be proved by the results of the evaluation of learning social studies (IPS). Before implementing the CAR, the percentage of students who get above 50% after the KKM is implemented by a class action jigsaw cooperative learning model increased to 78.6%. In the second cycle of pre test results showed that the percentage of students who get more value from KKM was 64.3% after the action was later increased to 92.9%.